2005
DOI: 10.1093/rheumatology/keh528
|View full text |Cite
|
Sign up to set email alerts
|

Moderately intensive exercise in a temperate pool for patients with rheumatoid arthritis: a randomized controlled study

Abstract: Pool exercise therapy of moderate intensity significantly improved muscle endurance in the upper and lower extremities in patients with RA, while no impact on aerobic capacity was found. However, the study population was small and there is a need for further studies with larger populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 33 publications
6
68
0
10
Order By: Relevance
“…Several studies have reported that grip force increases as a result of interventions (30,(37)(38)(39)(40)(41)(42). The results in the present study also indicate that increasing the grip force may result in reduced activity limitations.…”
supporting
confidence: 79%
“…Several studies have reported that grip force increases as a result of interventions (30,(37)(38)(39)(40)(41)(42). The results in the present study also indicate that increasing the grip force may result in reduced activity limitations.…”
supporting
confidence: 79%
“…Similarly, Neuberger et al showed that patients taking part in a 12-week class exercise program experienced significant amelioration in disease-related parameters, whereas home-based exercise did not have that result, probably because patients in this group exercised at a lower intensity (29). Indeed, most of the studies reporting positive effects of exercises on quality of life were supervised intervention trials (3,20,24), whereas most of the studies in which this outcome was not modified were home-based exercises (25). It is likely that supervised exercises result in higher adherence to the exercise program and positive group enthusiasm, explaining the trend of higher SMDs in subsets of trials with supervised intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 14 trials with cardiorespiratory aerobic exercise conditioning, the intervention fulfilled the dynamic exercise program criteria in 5 studies (5,8,20 -22). The control group underwent range of motion exercises in 3 studies (5,22,23), non-aerobic exercises in 1 study (24), education programs in 2 studies (3,25), and usual care in 8 studies (8,20,21,26 -30).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A associação de AR com outras doenças reumáticas, como LES, pode implicar em alterações na capacidade física, em virtude da presença de dor, da diminuição da força muscular, da propriocepção e da estabilidade mecânica, agravando o quadro de déficit do equilíbrio postural 12 . Ainda, outro estudo verificou que mulheres com FM, se comparadas a indivíduos sem a doença, apresentam déficit de equilíbrio postural e da autoconfiança por conta da dor e dos agravos causados pela patologia 13 .…”
Section: Pós-intervençãounclassified